Race and the American Story - Shonekan, Stephanie (Oxford University Press, Incorporated, 2024)
Race and the American Story provides a historically sensitive, culturally informed, and refreshingly novel treatment of race in the US. Combining the power of storytelling with the authors' expertise as scholars of politics and culture, this book shows how two very different personal stories relate to the American story--a story that is in danger of disintegrating in the twenty-first century
Description based on publisher supplied metadata and other sources